Hypercoagulation in Lung Cancer - Annisa Dian Harlivasari; Elisna Syahruddin (Jurnal Respirologi Indonesia, 2019)
Hypercoagulation with a clinical manifestation of Venous Thromboembolism (VTE) is a frequent complication of malignancy whose incidence has increased markedly these recent years. The occurrence of VTE is likely to be triggered by multiple pathways dominated by tissue factor (TF). The VTE itself can directly lead to patient mortality and becoming the cause of death in cancer patients. Furthermore, emerging data suggest that activation of coagulation in malignancy is integrally linked with tumor biology, host associated and cancer treatment particularly with anti-angiogenesis. The clinical hypercoagulable state is linked with prognosis in patients with lung cancer, including patients receiving systemic chemotherapy. (J Respir Indo 2019; 39(2): 130-9)